2015
DOI: 10.3329/bjp.v10i2.22285
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological basis for the folkloric uses of <i>Buxus wallichiana</i> in gastrointestinal, respiratory and vascular disorders

Abstract: <p><em>In vitro</em> study was carried out to explore the pharmacological basis of crude extract of <em>Buxus wallichiana </em>for its folkloric uses in gastrointestinal, respiratory and vascular disorders. In jejunum preparations, crude extract (0.03 ± 1.0 mg/mL) caused a transient spasmogenic effect followed by the spasmolytic effect at higher doses (3.0–10 mg/mL). In atropinized jejunum preparation, crude extract inhibited the spontaneous and K<sup>+ </sup>(80 mM)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This study has demonstrated that B. sempervirens possesses antispasmodic and prokinetic activities. Similar results were obtained in studies on Buxus wallichiana (a plant in the same genus) which is used for treating gastrointestinal, cardiovascular and respiratory illnesses [15].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This study has demonstrated that B. sempervirens possesses antispasmodic and prokinetic activities. Similar results were obtained in studies on Buxus wallichiana (a plant in the same genus) which is used for treating gastrointestinal, cardiovascular and respiratory illnesses [15].…”
Section: Discussionsupporting
confidence: 71%
“…The traditional use of B. sempervirens as a laxative and spasmolytic [2,15] formed the bases of this study. Results from phtochemical analysis showed that AqMeBS contains flavonoids, tannins, alkaloids and saponins.…”
Section: Discussionmentioning
confidence: 99%
“…Other plants traditionally used for asthma such as Viola odorata and Buxus wallichiana (Hussain et al, 2015) act by blocking Ca 2+ channel.…”
Section: Concentration Of Extractmentioning
confidence: 99%
“…For the assessment of calcium channel blockade, jejunum preparations were depolarized by exposing to high K + (80 mM), resulting in sustained contraction (Arshad et al, 2012;Hussain et al, 2015c). Ethanolic extract was applied in a cumulative manner to the sustained contractions to achieve concentration-dependent inhibitory response (Farre et al, 1991).…”
Section: Assessment and Conformation Of Ca 2+ Channel Blocking Activitymentioning
confidence: 99%